2012
DOI: 10.1111/ppl.12003
|View full text |Cite
|
Sign up to set email alerts
|

Leaf senescence in rice due to magnesium deficiency mediated defect in transpiration rate before sugar accumulation and chlorosis

Abstract: Magnesium (Mg) is an essential macronutrient supporting various functions, including photosynthesis. However, the specific physiological responses to Mg deficiency remain elusive. In this study, 2-week-old rice seedlings (Oryza sativa. cv. Nipponbare) with three expanded leaves (L2-L4) were transferred to Mg-free nutrient solution for 8 days. In the absence of Mg, on day 8, L5 and L6 were completely developed, while L7 just emerged. We also studied several mineral deficiencies to identify specific responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 47 publications
3
37
0
1
Order By: Relevance
“…Tang et al (2012) and Yang et al (2012) reported lower g s in Mg deficient Citrus plants. A decrease of g s was also reported by Kobayashi et al (2013). In their study on rice plants, Mg deficiency had a more pronounced effect on transpiration rates, as the latter declined earlier than assimilation rates.…”
Section: Leaf Gas Exchange and Leaf Water-use Efficiency Affected By supporting
confidence: 62%
“…Tang et al (2012) and Yang et al (2012) reported lower g s in Mg deficient Citrus plants. A decrease of g s was also reported by Kobayashi et al (2013). In their study on rice plants, Mg deficiency had a more pronounced effect on transpiration rates, as the latter declined earlier than assimilation rates.…”
Section: Leaf Gas Exchange and Leaf Water-use Efficiency Affected By supporting
confidence: 62%
“…Purple colouration by anthocyanins is a common signal induced by various stresses, not only in rapeseed (Chalker‐Scott, ; Gould, ). Even nutrient deficiency (e.g., N, P or Mg) can result in anthocyanin accumulation (Kobayashi et al., ; Lawanson, Akpe, Akindele, & Fasalojo, ; Lovdal, Olsen, Slimestad, Verheul, & Lillo, ). In this study, N deficiency, induced by the waterlogging stress, may be responsible for the anthocyanin formation of older leaves.…”
Section: Discussionmentioning
confidence: 99%
“…In plants well supplied with Mg only about 20% of the total Mg is bound to chlorophyll, whereas the remaining about 80% is present in more mobile forms. 49 Kobayashi et al, 50 reported that transpiration alleviation occurred before sugar accumulation and chlorosis in Mg deficient leaves.…”
Section: Plant Responses Under Magnesium Deficiencymentioning
confidence: 99%